Legal Protection for Property Buyers in Pre-Project Selling Schemes in Indonesia: An Analysis of Compliance with the Consumer Protection Act - Abraham Yazdi Martin; Henny Nuraeny; Andri Brawijaya (Ann Publisher, 2025)
Background. Pre-project selling has become a dominant marketing strategy in Indonesia’s property sector, yet it often exposes buyers to legal uncertainties, particularly regarding delayed construction and unmet contractual promises. Aim. This study examines the extent to which pre-project selling practices comply with Indonesia’s Consumer Protection Act and evaluates the adequacy of current legal safeguards for property buyers. Methods. Using a normative legal approach, the study analyzes statutory provisions, developer–consumer contracts, and relevant court decisions to identify compliance gaps and recurring legal issues. Results. The findings indicate that although the Act provides fundamental consumer rights, weak enforcement mechanisms, asymmetric information, and inadequate oversight allow developers to circumvent their obligations. Many contractual clauses tend to disadvantage buyers, and dispute resolution often results in limited remedies. Conclusions. Existing regulations do not sufficiently protect consumers in pre-project selling transactions, leaving buyers vulnerable to financial and legal risks. Strengthening regulatory oversight, standardizing contract terms, and enhancing sanctions for non-compliance are crucial to improving consumer protection. Implication. The study contributes to academic discourse on consumer law, provides policy insights for regulators, supports better awareness for society and property buyers, and offers a reference for international scholars examining consumer protection in emerging markets.